ASSA13-10-15 Association Between Polymorphism in the Chemokine CCL21 Gene Rs10972201 and Coronary Artery Disease in Chinese Han Population. (29th April 2013) - Wenzhi, Cai; Xiaolin, Zhang; Xueyao, Feng; Jing, Bai; Tengfei, Liu; Yaling, Han
Abstract : Background: Atherosclerosis is an inflammatory disease characterised by the formation of atherosclerotic plaques. Homeostatic chemokine CCL21 was up-regulated within the atherosclerotic lesions, which could potentially contribute to atherogenesis and plaque destabilisation with subsequent thrombus formation and development of acute ischemic events. Although CCL21 expression may be genetically determined, the relationship between CCL21 polymorphisms and the risk of coronary artery disease (CAD) is unclear. Objective: The aim of this study was to investigate the relationship between the polymorphism of CCL21 rs10972201 and the CAD in a Chinese Han population. Methods: Matched case-control study was conducted between January 2010 to September 2011 among 282 patients with CAD and 258 hospitalised controls. All the subjects had undergone coronary angiography, and inclusion criteria for CAD were ≥ 50% narrowing of the lumen of at least 1 of the major coronary arteries by coronary angiography. Additionally, angiographic severity of disease was deﬁned as 0-, 1-, 2- or 3-vessel disease based on the number of luminal narrowing ≥ 50% in the three major coronary arteries. The control subjects were selected from the subjects admitted to the hospital for the evaluation of chest pain, whose major coronary artery had no stenosis, and did not have any vascular disease. The groups were matched for age, sex, body mass index, smoking, hypertension, hypercholesterolemia, and diabetes. Polymorphic genotypes were determined by polymerase chain reaction and sequencing analysis. Results: The genotype frequencies of GG, AG and AA in CCL21 rs10972201 polymorphism were 83.33%, 15.96%, 0.71% in CAD group, 84.49%, 15.12%, 0.39% in the control respectively. The A allele frequency of CCL21 rs10972201 polymorphism allele in CAD cases and controls were 8.69% and 7.95% respectively. No significant differences in the genotype or allele frequencies were revealed between the two groups ( P = 0.864 and 0.659, respectively). Further stratification analysis between the polymorphism of CCL21 rs10972201 and angiographic severity of CAD also yielded negative results ( P > 0.05). Conclusions: This study indicates that the CCL21 rs10972201 polymorphism is unlikely to be a major contributor to the pathogenesis of CAD.